Morphology of Spicules of Phyrella sp. (Sea Cucumber) from Demak Waters, Central Java, Indonesia - Apriliani, Seka Indah; Widianingsih, Widianingsih; Trianto, Agus; Hartati, Retno (Universitas Diponegoro, 2025)
Phyrella is a genus of sea cucumbers that holds significant economic value and is widely exported for human consumption. Despite its importance, knowledge regarding the species diversity of Phyrella in Indonesian waters, particularly in Demak Waters, remains limited. This study aims to identify the Phyrella species found in this region through morphological analysis of spicules. The identification process involved examining the spicules present in the calcareous ring and various body parts, including the anterior, posterior, ventral, and dorsal regions. Spicules were observed using a light microscope at 100x magnification after dissolving body tissues with a sodium hypochlorite (NaOCl) solution to isolate their structure. The findings revealed four distinct spicule shapes: buttony, mensal, barbed, and barbed wire rod. These spicule characteristics are essential in distinguishing Phyrella species. Based on these morphological features, the sea cucumber species found in Demak Waters was identified as Phyrella fragilis. The results contribute to taxonomic studies and provide insights into the ecological role of Phyrella fragilis in marine ecosystems. Furthermore, this species has potential applications in the food, pharmaceutical, and cosmetic industries due to its rich nutritional content and bioactive compounds. Understanding its morphology and distribution can aid conservation efforts and sustainable resource management.